Transformation of Pancasila Student Profile: Integration of religious dimensions through school culture and character education in elementary schools - Indriani, Fitri; Cahyanti, Ganis; Tumiran, Mohd Amzari (Universitas Negeri Yogyakarta, 2024)
The transformation of the Pancasila Student Profile is a key effort in shaping the character and national identity of students in Indonesia. This study explores integrating religious dimensions into school culture to strengthen the implementation of the Pancasila Student Profile at the elementary school level. The research method used is a literature study, in-depth analysis of educational policies, school practices, and relevant character education theories. The focus of this study is on implementing religious values as an integral part of school culture and its impact on the formation of student attitudes and behaviours through the Pancasila Student Profile. The literature reviewed includes various studies and reports highlighting the importance of religious values in character education and models of success from schools that have successfully integrated this dimension. The study results indicate that integrating religious values into school culture significantly strengthens students' commitment to the principles of Pancasila and contributes to the formation of characters that are more virtuous, responsible, and caring about the social environment. This study concludes that effective transformation of the Pancasila Student Profile requires a holistic approach involving all school elements in instilling positive religious and cultural values. Practical recommendations for educators and policymakers include developing curricula sensitive to religious values and increased training for teachers to support effective integration in school settings.